Overexpression of aquaporin 4 in articular chondrocytes exacerbates the severity of adjuvant-induced arthritis in rats: an in vivo and in vitro study - Cai, Li (J Inflamm (Lond), 2017)
BACKGROUND: The dysfunction of articular chondrocytes is a crucial step in rheumatoid arthritis (RA) pathogenesis while its molecular mechanisms are not fully known. This study was aimed to investigate the expression of aquaporin 4 (AQP4) in articular chondrocytes of adjuvant-induced arthritis (AIA) rats and its involvement in AIA development. METHODS: Thirty rats were divided into normal and AIA group (n = 15). Rat AIA was induced by intradermal injection of complete Freund’s adjuvant and evaluated by secondary paw swelling and histological assessments on knee joint damage. Localization and protein expression of AQP4 in articular cartilage were examined by immunohistochemistry and western blot. In vitro study, AIA articular chondrocytes were cultured and treated with acetazolamide, an AQPs inhibitor. AQP4 protein level, cell proliferation and mRNA levels of type-II collagen (COII) and aggrecan were measured by western blot, MTT assay and real-time PCR, respectively. RESULTS: The results of immunohistochemistry and western blot indicated that AQP4 showed higher protein levels in cartilage tissues of AIA rats than that of normal rats. Correlation analysis revealed that AQP4 protein level in cartilage tissues of AIA rats remarkably correlated positively with secondary paw swelling on day 26 after AIA induction as well as pathological scores on joint damage. Additionally, acetazolamide treatment effectively decreased AQP4 protein level, increased cell proliferation and mRNA levels of COII and aggrecan, suggesting AQP4 inhibition by acetazolamide could normalize the dysfunction of AIA articular chondrocytes in vitro. CONCLUSIONS: Our data provide certain experimental evidence that AQP4 over-expression in articular chondrocytes aggravated AIA severity and might be a novel target for RA treatment.